Determinants of Employee Performance: Work Conflicts, Job Stress, and Job Satisfaction: Faktor Penentu Kinerja Karyawan: Konflik Kerja, Stres Kerja, dan Kepuasan Kerja - Wiwid Ida Risnawati; Mudji Astuti (Academia Open, 2022)
This study investigates the impact of work conflicts, job stress, and job satisfaction on employee performance in a quantitative research design, focusing on PT. Federal International Finance Group (Fif-Group) Sidoarjo. A sample of 30 employees was selected for the study. Multiple linear regression analysis, multiple correlation coefficient (R), and classical assumption tests were conducted using SPSS version 18. Primary data were collected through questionnaires employing a Likert scale, which underwent validity and reliability testing. The findings demonstrate that work conflicts, job stress, and job satisfaction significantly influence employee performance, with job satisfaction emerging as the most influential variable. These results contribute to a better understanding of the factors shaping employee performance and have implications for organizations seeking to enhance productivity and well-being in the workplace. Highlights: The study examines the impact of work conflicts, job stress, and job satisfaction on employee performance. Quantitative analysis using multiple linear regression and correlation coefficients is employed to analyze the data. The findings reveal that job satisfaction has the strongest influence on employee performance. Keywords: Employee performance, Work conflicts, Job stress, Job satisfaction, Quantitative analysis